A new species of Sphenomorphus Fitzinger, 1843 (Squamata: Sauria: Scincidae) from Vietnam - Nguyen, Truong Quang; Nguyen, Khoi Vu; van Devender, Robert Wayne; Bonkowski, Michael; Ziegler, Thomas (Zootaxa, 2013)
A new forest skink species of the genus Sphenomorphus is described from Kon Tum Plateau, southern Central Vietnam. Sphenomorphus sheai sp. nov. is similar to the other montane skink species from the Indochina region, Lygosoma veunsaiensis, Scincella apraefrontalis, Sphenomorphus tetradactylus, and Sphenomorphus tridigitus, in having a small size and the absence of external ear openings. However, the new species is differentiated from aforementioned species and other members of Sphenomorphus from China and mainland Southeast Asia by a unique suite of morphological characters. The discovery of S. sheai brings the total species number of Sphenomorphus known from Vietnam to twelve.